FGF23 level in poultry chicken, a systematic review and meta-analysis - Poorhemati, Hossein; Ghaly, Melody; Sadvakassova, Gulzhakhan; Komarova, Svetlana V. (Frontiers in Physiology, 2023)
In vertebrates, fibroblast growth factor 23 (FGF23) is a phosphate regulating hormone closely linked to calcium regulation by vitamin D and parathyroid hormone (PTH). Although phosphorus, calcium and vitamin D are important for poultry well-being, relatively little is known about their levels of FGF23. Our objective was to quantitatively estimate the blood FGF23 level in birds, and to examine its relationship to diet and blood levels of other components of phosphate and calcium homeostasis. A systematic search of Agricola, Embase and Medline identified 86 studies published between 2015 and 2022 that were focused on FGF23 in birds, from which 12 manuscripts reporting data for 60 independent groups of chickens were included in the analysis. FGF23 levels were 256 pg/ml (Confidence interval (CI): 215, 297) in broilers ( 39datasets containing 435 birds), and 256 pg/ml (CI: 178, 339) in egg-laying hens (21 datasets containing 208 birds). FGF23 levels did not correlate with dietary phosphorus, calcium, or vitamin D, or with plasma calcium or PTH. FGF23 levels demonstrated a trend to positively correlate with plasma phosphate and a strongly and positive correlation with plasma vitamin D. This study provides normative estimates of FGF23 levels in poultry birds and new insights into the regulation of calcium and phosphate homeostasis.